PANDUAN KOMUNIKASI UNTUK BERBICARA YANG MENDIDIK (REKONDISI KAJIAN PSIKOLOGI DAN AKHLAK) - Syafnan, Syafnan (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2014)
To guide communication to speak in education is an effort reconditioning psychology and character. There are three major ideas in it: 1) how to communicate children right from what to avoid, to support, to motivate be intensive, eye contact and wanderful and harmony given words. Meanwhile for teenagers or yoaungsters, we need to give them chance to speak much more and to listen actively and to communicate empatically. For adult, is to guide them comprehensive communication and speech acts.